Customer Perception toward Digital Financial Services: A Case of Pokhara, Nepal (Butwal Campus Journal, 2023)
The banking industry is undergoing a significant digital transformation, embracing digital finance as a pivotal aspect of the financial system. Because of digitalization, the financial sector has seen a steady evolution in the provision of financial services over the past few decades. Digital finance service providers offer several new financial products, financial businesses, finance-related software, and unique modes of client communication and interaction. This study aims to assess customer perceptions and identify the key factors influencing their views on digital finance. This study followed a quantitative research design. It is based on primary data collected from 211 respondents through a field survey using a researcher-administered questionnaire in the Pokhara Valley of Nepal. Descriptive statistics and inferential statistics were applied to analyze the data using SPSS software. The study found security, convenience, and adaptability have a positive and significant influence on digital finance, with security having the most substantial impact. The findings contribute to the understanding of the factors influencing customer perceptions and adoption of digital financial services (DFS), offering valuable implications for policymakers, financial institutions, and service providers aiming to enhance the digital finance landscape in both urban and rural communities.